A fourth-order PDE-based non-linear fi lter for speckle reduction from Optical Coherence Tomography images - Srivastava S.; Srivastava R.; Sharma N.; Singh S.K.; Sharma S. (My University, 2025)
In this paper, a fourth-order PDE-based non-linear fi lter for speckle reduction from Optical Coherence Tomography (OCT) images is proposed in a variational framework. The speckle noise pattern in OCT images is distributed according to Rayleigh's Probability Distribution Function (pdf). The initial condition of the proposed PDE-based fi lter is the speckle noised OCT images and the output is the better quality speckle reduced image. For digital implementations, the proposed scheme is discretised using the fi nite difference scheme. The performance comparison of the proposed scheme with other standard speckle reduction techniques such as the Lee fi lter, the Frost fi lter, the Kuan fi lter, the SRAD fi lter, the homomorphic Wiener fi lter and homomorphic versions of the anisotropic diffusion based fi lter, the non-linear complex diffusion-based fi lter and the fourth order PDE-based fi lter is also presented. The obtained results justify the applicability of the proposed scheme.